Fall Prevention Knowledge, Attitude, and Practices of Community Stakeholders and Older Adults - Sharon S. Laing; Ilene F. Silver; Sally York; Elizabeth A. Phelan (Journal of Aging Research)
We assessed knowledge, attitude, and provision of recommended fall prevention (FP) practices by employees of senior-serving organization and participation in FP practices by at-risk elders. The Washington State Department of Health administered structured telephone surveys to 50 employees and 101 elders in Washington State. Only 38% of employees felt “very knowledgeable” about FP, and a majority of their organizations did not regularly offer FP services. Almost half (48%) of seniors sustained a fall within the past 12 months; however, one-third perceived falling to be among their least important health concerns, and most had minimal working knowledge of proven FP practices. Seniors who perceived avoiding falls as important to their well-being were more likely to participate in practices about which they had the least knowledge (risk assessment, medication management). Increased awareness and availability of FP services might help engage older adults in FP practices and reduce the adverse effects of falls.